Analisis Yuridis Terhadap Rumusan Jarimah Pemerkosaan dalam Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat - Azkha, Umarani; Abbas, Syahrizal; Din, Mohd. (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
This research aims to predict the extent of the punishment disparity probability in the Qanun Jinayat's rape formula as a consequence of the breadth of the formula and to determine the construction of the definition and classification method of the classical Islamic jurisprudence’s az-zina bil-ikrah formula and the Qanun Jinayat’s rape formula as a consequence of radical differences between the two coercive sexual delicts that are formed based on Islamic law. This research is normative legal research by using statute and comparative approach. The research results showed that the Qanun Jinayat’s rape formula has the punishment disparity probability in the same delict, the disparity in delicts those have same seriousness gradation, the disparity of punishment imposed by one judges panel, the disparity of punishment imposed by different judges panel for the same delict and the disparity of punishment in different actions in one delict formula with different gradations of seriousness. The definition and classification of az-zina bil-ikrah are constructed through the bayani method, while the definition and classification of the rape are constructed through the istishlahi method.